Immunohistochemical localisation of FMRF-amide-like peptide in the brain of icefish and red blooded Antarctic Teleosts - MASINI, MARIA ANGELA; M. STURLA; F. RICCI; B. M. UVA (Polar Biology, 2005)
The distribution of Phe-Met-Arg-Phe-NH2 (FMRF-amide) -like immunoreactivity was investigated by indirect immunofluorescence technique using the molluscan FMRF-amide antibody in the brain of icefish (Pagetopsis macropterus and Chionodraco hamatus used as positive control) and red blooded (Trematomus bernacchii, Gymnodraco acuticeps, Histiodraco velifer, Cygnodraco mawsoni) Antarctic Teleosts. Immunoreactive perikarya were localised in the ventral thalamus, in the hypothalamus (preoptic and periventricular regions) and in the intermedioventral rhombencephalon (vagal motor nucleus) as well as in the telencephalon and in the mesencephalon. Positive nerve fibres were seen to project towards the caudal brainstem to reach the rhombencephalon. No differences were observed in the immunopositivity of FMRF-amide new distribution in the Antarctic Teleosts examined. In the icefishes the immunoreaction was stronger than in the hemoglobin-rich Teleosts. The distribution patterns of the FMRF-amide immunostaining suggest that this peptide may play a pivotal role in the cardiovascular regulation in the Antarctic Teleosts.